Implementasi Kebijakan Penyelesaian Retur Surat Perintah Pencairan Dana pada Kantor Pelayanan Perbendaharaan Surabaya 1 - fitriana, Nur Azizah Safiq; Muljanto, Muhammad Agus (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
In the research abstract, the author explains the policy of resolving SP2D returns in state financial management carried out by the Minister of Finance as the State General Treasurer through the State Treasury Service Office (KPPN). KPPN is part of the Directorate General of Treasury at the Ministry of Finance, directly related to the Head of the Regional Office of the Directorate General of Treasury. On the other hand, state ministries/institutions involve Work Units (Satker) as part of their organizational structure, responsible for activities that use APBN funds. This research uses a descriptive qualitative method, which focuses on describing, analyzing, and understanding more in-depth data from interviews and observations regarding the issue of SP2D returns. The aim is to understand the root causes of SP2D returns and the process of resolving them at KPPN Surabaya I through analysis of data collected at the research location. We as writers refer to the theory of George C. Edward III's theory that highlights communication, resources, disposition, and bureaucratic structure as factors that influence the success of policy implementation. In this study, the bank section aims to improve the service standards that have been implemented to achieve better results.